Group A Streptococcal Vir Types Are M-Protein Gene (emm) Sequence Type Specific - Gardiner, Don L. (American Society for Microbiology, 1998)
The M-protein genes (emm genes) of 103 separate impetiginous Streptococcus pyogenes isolates were sequenced and the sequence types were compared to the types obtained by Vir typing. Vir typing is based on restriction fragment length polymorphism (RFLP) analysis of a 4- to 7-kb pathogenicity island encoding emm and other virulence genes. By using both HaeIII and HinfI to generate RFLP profiles, complete concordance between Vir type and emm sequence type was found. Comparison of the emm sequences with those in GenBank revealed new sequence types sharing less than 90% identity with known types. Diversity in the emm sequence was generated by corrected frameshift mutations, point mutations, and small in-frame mutations.